Carboxymethyl chitosan grafted trisiloxane surfactant nanoparticles with pH sensitivity for sustained release of pesticide. (1st September 2020) - Zhao, Ming; Zhou, Hongjun; Chen, Long; Hao, Li; Chen, Huayao; Zhou, Xinhua
Highlights: CMCS-AGE-TSS is prepared as nanopesticide carriers by radical grafting reaction. Nanoparticles improve the dispersibility and adhesion of avermectin on leaf. Encapsulation improves the stability of avermectin under ultraviolet light. CMCS-AGE-TSS @ AVM forms a pH-responsive controlled release pesticide system. Abstract: A trisiloxane surfactant (TSS) was grafted onto an intermediate, formed by the reaction of allyl glycidyl ether (AGE) with carboxymethyl chitosan (CMCS), to obtain amphiphilic CMCS-AGE-TSS. Avermectin (AVM) was used as a model pesticide and CMCS-AGE-TSS@AVM nanoparticles were prepared by self-assembly. The structures and morphologies of the nanoparticles were studied by FT-IR and 1 H NMR spectroscopy, XRD, SEM, TGA, DSC, and DLS techniques. The average particle size of CMCS-AGE-TSS@AVM was 210 nm, with encapsulation efficiency of 66 %. With increase in TSS content, the contact angle on the leaf surface decreased from 73.62° for CMCS to 49.32° for CMCS-AGE-TSS. The half-life of AVM encapsulated in the polymer shell increased from 45 min to 83 min. Moreover, sustained release of the drug showed a significant response to pH. Finally, the difference in toxicities between CMCS-AGE-TSS@AVM and pure AVM was not significant.